Science Learning Achievement; Three Dimension-Media Innovation in Contextual Learning Approach - Widiana, I Wayan; Kusmariatni, Nyoman; Sedana, Dewa Nyoman; Riastini, Putu Nanci (Journal of Education Research and Evaluation, 2019)
Science learning achievement is low in some elementry schools in Bali and it is suspected that learning process is one of the factors that has caused this. Hence, there is a need for innovations in learning to improve learning process which has so far taken place (conventional). This study wasa aimed at finnding out the difference in science learning achievement  between students who are taught  through contextual learning which uses three dimension media and those who are taught through conventional learning..this is a quasi-experimental research with non equivalent post-test only control group design. The population used in this study was the fourth grade students af elementary schools in Gugus 1 Singaraja with the total number of eight schools. The sample in this study was selected  using  random sampling. Out of the eight schools in Gugus 1 Singaraja, two schools wereselected, namely SD No. 5 Banyuning as experiment group and SD No.6 Banyuning as conrol group.. the data gathered inthis study was in the form of science learning achievement. The instrument used to collect the data was an objective test or multiple choice.  The data were analyzed  using inferential statistics or t-test.  The result showed that  science learning achievement in the group where  three dimension media were used  had  the mean score of 20.75 , which is higher than  the group where conventional learning was used , whose mean score was 17. 08. This result  was confirmed by hypothesis testing in which it was obtained that tobs. > tc.v.. This means that  the implementation of contextual  learning approach  which was aided with three dimenisionmedia had  a positive effect on  science learning achivement.